Interconnected ZrO2 doped ZnO/TiO2 network photoanode for dye-sensitized solar cells - Abdulmenan M. Hussein; Anastasiia V. Iefanova; Ranjit T. Koodali; Brian A. Logue; Rajesh V. Shende (Energy Reports, 2018)
In this study, ZrO2 surface modified ZnO/TiO2 composite film is adapted as photoanode in dye sensitized solar cells (DSSCs) and compared with un-passivated ZnO/TiO2 DSSC performance. The performance is investigated by dark and photocurrent density–voltage ( J–V) characteristics, quantum efficiency and electrochemical impedance spectroscopy. The J–V characteristics shows that DSSCs with ZrO surface passivation produces significantly high open-circuit voltage of 0.87 V, short-circuit current density of 13.6 mA cm-2, fill factor of 0.65 and a power conversion efficiency of 6.97% under simulated AM1.5 solar irradiation. The higher onset potential in the dark, larger open-circuit potential under illumination, and an enhancement in power conversion efficiency strongly suggests an efficient suppression of back electron transfer from the conduction band of the hetero-phase junctions to the oxidized species in the electrolyte as established by dark and illuminated J–V characteristics. Thus, the oxidized dye molecules are readily regenerated by a redox couple dissolved in an electrolyte, allowing more photon excitation by dye molecules. The electrochemical impedance data extracts further provide additional evidence of the enhancement in photocurrent and lower charge carrier resistances observed in ZrO2/ZnO/TiO2/dye photoelectrode. With the ZrO2 surface modification, main loss mechanism in the device is suppressed and backward recombination reaction is minimized.
Keywords: 330; Dark current; Equivalent circuit model; Mesoporous films dye-sensitized solar cells; ZrO passivated ZnO/TiO hetero-phase composite